A Study on Psychological Characteristics of Cricket Players based on their Specialist Roles: The Role of Psychological Characteristics in Cricket Players' Performance (Journal of Advances and Scholarly Researches in Allied Education, 2022)
According to research linking psychological traits to peak performance, elite and successfulathletes are more driven, devoted, self-assured, focused, and able to perform at their best underpressure than non-elite and unsuccessful competitors. The constructive application of mental-skillinstruction may enhance the mental components of performance of functional activities in sport. Adegree of fluidity between the various mood states of participation in the organisation andimplementation of task-related abilities is made possible by personalised mental skill preparation forlearners. In addition to improving mission success, a participant's ability to control the behavioural andemotional aspects of competition serves as a mental cornerstone for self-belief and wellbeing.